Examining whether lung screening changes risk perceptions: National Lung Screening Trial participants at 1‐year follow‐up1. Issue 7 (20th December 2012) - Park, Elyse R.; Gareen, Ilana F.; Jain, Amanda; Ostroff, Jamie S.; Duan, Fenghai; Sicks, JoRean D.; Rakowski, William; Diefenbach, Michael; Rigotti, Nancy A.
Abstract BACKGROUND: The National Lung Screening Trial (NLST) research team reported reduced lung cancer mortality among current and former smokers with a minimum 30 pack‐year history who were screened with spiral computed tomography scans compared with chest x‐rays. The objectives of the current study were to examine, at 1‐year follow‐up: 1) risk perceptions of lung cancer and smoking‐related diseases and behavior change determinants, 2) whether changes in risk perceptions differed by baseline screening result; and 3) whether changes in risk perceptions affected smoking behavior. METHODS: A 25‐item risk perception questionnaire was administered to a subset of participants at 8 American College of Radiology Imaging Network/NLST sites before initial and 1‐year follow‐up screens. Items assessed risk perceptions of lung cancer and smoking‐related diseases, cognitive and emotional determinants of behavior change, and knowledge of smoking risks. RESULTS: Among 430 NLST participants (mean age, 61.0 years; 55.6% men; 91.9% white), half were current smokers at baseline. Overall, risk perceptions and associated cognitive and emotional determinants of behavior change did not change significantly from prescreen trial enrollment to 1‐year follow‐up and did not differ significantly by screening test result. Changes in risk perceptions were not associated with changes in smoking status (9.7% of participants quit, and 6.6% relapsed) at 1‐year follow‐up. CONCLUSIONS: Lung screening did not change participants' risk perceptions of lung cancer or smoking‐related disease. A negative screening test, which was the most common screening result, did not appear to decrease risk perceptions nor provide false reassurance to smokers. Cancer 2013. © 2012 American Cancer Society.